2012
DOI: 10.5483/bmbrep.2012.45.12.235
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of protein tyrosine phosphatases in adipogenesis: New anti-obesity targets?

Abstract: Obesity is a worldwide epidemic as well as being a major risk factor for diabetes, cardiovascular diseases and several types of cancers. Obesity is mainly due to the overgrowth of adipose tissue arising from an imbalance between energy intake and energy expenditure. Adipose tissue, primarily composed of adipocytes, plays a key role in maintaining whole body energy homeostasis. In view of the treatment of obesity and obesity-related diseases, it is critical to understand the detailed signal transduction mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…The differentiation of preadipocytes into mature fat cells is regulated by a highly orchestrated gene An increasing number of obesity studies have reported the involvement of several types of protein phosphatases in adipogenesis, including serine/threonine and tyrosine phosphatases [16], and they are increasingly considered as biochemical "on" or "off" switches and key regulators in intracellular signaling cascades during adipogenic differentiation [16]. To date, it has been shown that several protein phosphatases are up-regulated in and promote adipocyte differentiation [17].…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of preadipocytes into mature fat cells is regulated by a highly orchestrated gene An increasing number of obesity studies have reported the involvement of several types of protein phosphatases in adipogenesis, including serine/threonine and tyrosine phosphatases [16], and they are increasingly considered as biochemical "on" or "off" switches and key regulators in intracellular signaling cascades during adipogenic differentiation [16]. To date, it has been shown that several protein phosphatases are up-regulated in and promote adipocyte differentiation [17].…”
Section: Discussionmentioning
confidence: 99%
“…There are two distinct types of adipocytes, white and brown adipocytes, which have opposite functions with regard to the energy balance (Bae et al, 2012;Kim et al, 2015a). White adipocytes store excess energy as triglycerides in lipid droplets, whereas brown adipocytes release energy in the form of heat through thermogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue, which is composed mostly of adipocytes, is a major endocrine organ and plays a key role in energy homeostasis. Two types of adipose tissue, white adipose tissue (WAT) and brown adipose tissue (BAT), have been identified [1] . In practice, obesity does not depend on body weight but depends on either the number of white adipocytes or the amount of WAT.…”
Section: Introductionmentioning
confidence: 99%